THE OPPORTUNITIES AND CHALLENGES OF XI'AN CITY IMAGE BUILDING THROUGH THE GOVERNMENTAL PERSPECTIVE IN TIK-TOK PLATFORM: A SYSTEMATIC NARRATIVE REVIEW - Li Mengjiao; Afeez Nawfal Mohd Isa, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Background: In the context of the rapidly advancing 5G era, mobile short video platforms have become integral to modern media communication. Tik-Tok, a prominent social media app in China with over a billion daily users, has transformed how people access information. This evolution has profound implications for shaping a city's image, which holds sway over a region's influence in an increasingly globalized world. Objective: This systematic narrative literature review explored empirical evidence on city image building and communication on Tik-Tok platform. And also gave a new strategy from governmental perspective for the building and dissemination of Xi'an's city image on the Tik-Tok platform in the future. Participants and setting: This research selected the article on the Scopus, and CNKI databases. The review is limited to articles published in journals in English and Chinese during the three years from January 1, 2020 to January 1, 2023. Methods: The systematic approach to literature reviewing was utilized 'Systematic Narrative Review'. This research used content analysis to systematically organize the literature over the last three years. Results: The review summarizes the findings of the selected studies, which show that governments have the ability to strategically use the Tik-Tok short-form video platform to intangibly build and communicate the urban image of a specific region in the face of the challenges of developing urban communication. Conclusion: The review highlights that short video-driven city image construction and communication pose noteworthy opportunities and challenges. This warrants deeper scholarly investigation. Through studying Xi'an's TikTok-based city image building, this paper explores governmental strategies for content creation and communication.